The Penelopiad - Atwood, Margaret, 1939- (Myths (Canongate Publishing), 2005)
The story of Odysseus' return to his home kingdom of Ithaca following an absence of twenty years is best known from Homer's Odyssey. Odysseus is said to have spent half of these years fighting the Trojan War and the other half wandering around the Aegean Sea, trying to get home. But what of his wife, Penelope? The author has chosen to give the telling of the story to Penelope and to the twelve hanged Maids.